Etiological and clinical features of pediatric hypertension in a tertiary hospital of Central India - Goel, Manjusha; Choubey, Bharati; Meena, Kiran; Agarwal, Amit (Indian Journal of Child Health, 2019)
Background: Hypertension (HTN) in children and adolescents seems to have increased in the past few decades. Although the prevalence of essential HTN has increased, secondary causes account for majority of childhood HTN. Essential HTN in childhood is a diagnosis arrived at by excluding the known causes of secondary HTN. Objectives: The objectives of this study were to study the etiology and clinical features of childhood HTN in admitted children. Materials and Methods: This observational prospective study was carried out at a tertiary care referral center of Central India. All children of 1–12 years of age admitted in hospital in the study period were screened for HTN. Those found to be hypertensive were studied for etiology and clinical features. Results: A total of 112 children were found to be hypertensive, 54 were in 1–6 years of age group and 58 were in 7–12 age group. Male-to-female ratio was 62:50, 95 had secondary HTN and no definitive cause of HTN could be found in 5% of patients. Mean blood pressure was 124/84. Majority (75%) of patients were in Stage II HTN, 25% of patients were in hypertensive crisis. About 69% had renal etiology, 25% central nervous system (CNS), 1% endocrine, and unidentified 5%. Conclusion: The most common etiology of hypertensive emergency is chronic kidney disease followed by acute glomerulonephritis.